Current Concepts in the Treatment of Renovascular Hypertension - Herrmann, Sandra M (Am J Hypertens, 2018)
Renovascular disease (RVD) remains a major cause of secondary and treatment-resistant hypertension. Most cases are related either to fibromuscular or atherosclerotic lesions, but a variety of other causes including arterial dissection, stent occlusion, and embolic disease can produce the same syndrome. Recent studies emphasize the kidney’s tolerance to moderate flow reduction during antihypertensive drug therapy and the relative safety of medical therapy to control blood pressure. Several prospective trials in moderate RVD fail to identify major benefits from endovascular revascularization for moderate atherosclerotic disease. However, high-risk and progressive renovascular syndromes are recognized to be relatively refractory to medical therapy only and respond better to combining renal revascularization with ongoing medical therapy. Clinicians caring for complex hypertension should be familiar with pathogenic pathways, imaging techniques, and a rational approach to managing renovascular hypertension in the current era.